Gunshot Defense Wounds: Three Case Reports and a Literature Review - Laura Ambrosi; Simona Nicolì; Davide Ferorelli; Roberto Vaglio; Biagio Solarino; Marcello Benevento (Forensic Sciences)
Defense wounds generally occur when a victim attempts to protect vital organs and blood vessels during an assault, and are therefore typically located on the forearms or hands. Gunshot-induced defense wounds are less frequent compared to stab wounds, which have been extensively described in the literature. We present three cases where victims unsuccessfully attempted to defend themselves from gunshots, and where the detailed description of injuries played a key role in the reconstruction of the crime scenes. In the first case, a man was shot with a smooth-bore shotgun, presenting a “through-and-through” gunshot wound on the lateral surface of the left forearm and a large gaping wound on the posterior surface of the same forearm. The second and third cases involved two men who were shot with handguns. The first displayed an entrance wound on the dorsal surface of the right hand, with burned edges and smoke soiling, and an exit wound on the palmar surface. The second case involved two wounds on the left hand: one on the dorsum and the other on the palm. To the best of our knowledge, few studies in the literature emphasize the role of gunshot defense wounds in aiding the reconstruction of crime dynamics. The cases presented in this study highlight the importance of precisely defining the pathological and morphological features of the wounds, as well as the bullet trajectories, to accurately identify defense wounds. These findings are valuable for reconstructing the dynamics of the assault and providing critical information to the public prosecutor.